Descriptive Analysis of Physics Learning Outcomes of Geography Department Students in the Basic Physics Course Using a Contextual Approach - Sanusi, Dirgah Kaso; Sri Agustini; Ihfa Indira Nurnaifah; Riskawati; Ahmad Yani (Journal of Physics Education : Review and Research, 2025)
This study aims to describe the learning outcomes of students in the Basic Physics course implemented through a contextual approach. This approach was applied to connect physics concepts with real-world situations in order to enhance students’ conceptual understanding. The research employed a quantitative descriptive method involving 62 students from the Geography Department, Faculty of Mathematics and Natural Sciences, State University of Makassar, as research subjects. Data were collected through an essay-type achievement test that assessed conceptual mastery and the ability to apply physics principles. The results showed that 11.29% of students were in the “very good” category, 32.26% in the “good” category, 24.19% in the “fair” category, 19.35% in the “poor” category, and 12.90% in the “very poor” category. These findings indicate that the majority of students achieved results ranging from good to fair, demonstrating the effectiveness of the contextual approach in improving learning outcomes. The contextual approach helps non-physics students bridge the gap between theory and reality while shifting their learning paradigm from passive to active and reflective. Through direct experiences and analysis of environmental phenomena, students are better able to construct knowledge and develop interdisciplinary scientific thinking skills. Keywords: contextual approach, learning outcomes, basic physics, descriptive analysis